Effect of Storage Duration and Seed Type on the Viability and Growth of Agave (Agave sisalana L. Perrine) from In Vitro Culture - Mala Murianingrum; Parnidi Parnidi; Moch. Machfud; Fatkhur Rochman; Marjani Marjani; Bambang Heliyanto; Rully Dyah Purwati (The University of Lampung, 2025)
Agave seeds have a relatively short lifespan, thus require appropriate storage methods to maintain their viability and germination capacity. This study aimed to identify the optimal combination of storage duration and seedling treatments to preserve seedling quality and growth performance of agave. The experiment was conducted in a factorial randomized complete design with three replications. Each experimental unit consisted of 10 plants. The first factor was storage duration (0, 21, and 35 days). The second factor was seedling treatments involving seeds with: (1) complete leaves and roots, (2) complete leaves and half roots, (3) top leaves and half roots, (4) complete leaves without roots, and (5) top leaves and no roots. The seedlings were stored in a greenhouse with average temperature 25.67 °C and relative humidity 82.92%. The observed parameters included weight loss, germination percentage, seedling height, number of leaves, leaf length and width, number and length of roots, and fresh weight after 45 days of planting. The results showed that storage duration and root or leaf trimming significantly affected seed viability and seedling growth. Storage for 21 days combined with full leaves and half roots produced the highest germination percentage, growth performance, and fresh weight. Agave seeds can be stored for up to 35 days while maintaining high viability, and different seed types stored for 35 days still exhibited 100% germination.